Anecdotes of an Obsolete Object, a Thing Astir Called Book - Paulina Aroch Fugellie ([sic])
What is a book? Perhaps the notion refers firstly to an articulate format: to a substantive amount of printed pages bound together. Yet it also presupposes an articulate discourse: these pages are bound together for a reason, they have a single organizing principle in the conceptual as in the material level. The order in which the pages are arranged corresponds to the gradual spinning out of an overall sense. Furthermore, this coherent material and discursive entity circulates in social worlds, becoming charged with different attributes according to context. A consistent symbolic role in a given time and place may lead a book to operate as the book, or at least allow the generic idea of the book to act as a constant mediation in our relationship with any particular volume. Homi Bhabha, for example, has described how “the English book” – a blanket reference to canonical Western texts such as The Bible – impacted the postcolonial contexts in which it was introduced. According to Bhabha, the English book is emblematic of original truth, whether it be the word of God, the entrance into history by way of the written record, or the universal truths proclaimed by humanist literary traditions. All these truths tend to become reified by means of the foreign, imposed, printed text in contexts of reception that hold different configurations of orality and writing (102-122).